O trabalho e o trabalhador na dramaturgia de Plínio Marcos: Dois perdidos numa noite suja - Salgueiro, José Estevam (2013)
This study seeks to identify and analyze what senses and meanings concerning the issue labor and worker are present in Plinio Marco s play Two lost in a dirty night (1966), based on the hypothesis that, through the political and social characteristics of the author s work, the issue of labor/worker constitutes one of the central dramatic cores of this text. The choice of the author and text is due to its historical and aesthetic importance in the universe of the Brazilian dramaturgy: the protagonists are outcast characters from the Brazilian society. This study discusses the relation among work, author and audience, choosing to focus on the analysis of the work (text), as proposed by the analytical objective method created by Vigotski, building scenic units which allows its application. The study also presents reflections on the relation between Art and History, Psychology and Politics. In a particular chapter it addresses the theatrical context at the time of the premiere of the text, aiming at characterizing the audience that received and echoed it. The results obtained prove the initial hypothesis, demonstrating the centrality of the issue labor / worker in the dramatic composition of the text